Energetic physiology mediates reproductive decisions in a long-lived, capital-income breeding seaduck - Hennin, Holly Lynn (University of Windsor, 2016)
Life history decisions are constrained by the allocation of limited resources to multiple functions, generating life history trade-offs. Individuals better able to acquire or manage endogenous resources are expected to optimize these trade-offs more efficiently, have higher performance and therefore achieve higher fitness. However, we still know little about how and why different individuals modulate energetic management to optimize breeding decisions. Physiology mediates the relationship between the individual and its environment, and therefore energetic physiology in particular is thought to be a prime candidate for regulating life history decisions. Baseline corticosterone is a hormone that mediates energetic balance and represents an individual's energetic demand. Plasma triglycerides are an energetic metabolite representing an individual's relative fattening rate and therefore their ability to meet energetic demands during costly life history stages. Together these two traits can represent an individual's "energetic physiology". My thesis uses a combination of correlative and manipulative techniques to determine the role of energetic physiology in mediating variation in a key life history decision: breeding phenology. To field-test predictions within the framework of the Physiology/Life History nexus I worked with a wild population of Arctic-nesting common eiders (Somateria mollissima), a diving seaduck with a mixed capital-income breeding strategy, at East Bay Island, NU, Canada. I found that baseline corticosterone and plasma triglycerides increase across the pre-laying period, likely to support the high energetic demands for investing in reproduction. Further, these traits interact to optimize the timing of breeding on an individual basis. Using a captive seaduck system to prepare for field experiments, I confirmed that I could experimentally elevate corticosterone within a baseline range and produce a concomitant increase in body mass. Using this experimental approach, I elevated baseline corticosterone ...